Characterisation of Y-PSZ and PR-doped Y-PSZ obtained by unconventional methods for sofc applications - Badenes, J. A.; Benet, P.; Sorlí, S.; Tena, M. A.; Monrós, G. (Boletín de la Sociedad Española de Cerámica y Vidrio, 2004)
The effect of method of preparation, including the traditional ceramic method and several sol-gel methods have been studied on the molar composition (ZrO2)0.92(Y2O3)0.04 and (ZrO2)0.82(Y2O3)0.04(Pr2O3)0.05 praseodymium doped samples. Powder fired at 500ºC was sieved at 60 μm, uniaxialy pressed and fired at 1.600ºC for 2h. The resulting compacts were characterised by XRD, SEM-EDX, density measurements, toughness strength and Vickers microhardness. The results indicate that colloidal samples stabilises tetragonal zirconia polymorph showing the best densification and electrical conductivity behaviour, praseodymium addition stabilises cubic zirconia improving the microhardness and densification of the material. Se ha estudiado el efecto del método de preparación, incluyendo el método cerámico tradicional y varios métodos sol-gel, sobre las composiciones (ZrO2)0.92(Y2O3)0.04 y (ZrO2)0.82(Y2O3)0.04(Pr2O3)0.05. Los polvos calcinados a 500ºC se tamizaron a 60 μm, se prensaron uniaxialmente y se sinterizaron a 1600ºC durante 2h. Los compactos resultantes se caracterizaron mediante XRD, SEM-EDX, medidas de densidad, tenacidad y microdureza Vickers. Los resultados indican que en las muestras coloidales se estabiliza el polimorfo tetragonal de la circona mostrando la mejor densificación y el mejor comportamiento en conductividad eléctrica. Las adiciones de praseodimio estabilizan la circona cúbica mejorando la microdureza y densificación del material.